A pragmatic pipeline for drug resistance and lineage identification in Mycobacterium tuberculosis using whole genome sequencing. - Linzy Elton; Alp Aydin; Neil Stoker; Sylvia Rofael; Letícia Muraro Wildner; Jabar Babatunde Pacome Agbo Achimi Abdul; John Tembo; Muzamil Abdel Hamid; Mfoutou Mapanguy Claujens Chastel; Julio Ortiz Canseco; Ronan Doyle; Giovanni Satta; et al. (PLOS Global Public Health, 2025)
Delays in accurate diagnosis of drug resistant tuberculosis (DR-TB) can hinder treatment. Whole genome sequencing (WGS) provides more information than standard molecular and phenotypic testing, but commonly used platforms are expensive to implement, and data interpretation requires significant expertise. We aimed to optimise a TB WGS diagnostic pipeline balancing user-friendliness, cost-effectiveness and time to results, whilst ensuring accuracy. Growth conditions, DNA extraction protocols and Oxford Nanopore Technologies (ONT) library preparation kits were compared. ONT was compared with Illumina protocols. Software for basecalling and analysis were evaluated to find the most accurate resistance SNP and lineage predictor. Optimally, a spin-column CTAB DNA extraction method was combined with the RBK110.96 library preparation kit, high accuracy (HAC) basecalling and data analysis using TB-Profiler. Compared with Illumina, the pipeline was concordant for 16/17 (94%) isolates (lineage) and for 17/17 (100%) isolates (resistance SNPs). Our pipeline was 71% (12/17) concordant with phenotypic drug susceptibility test (DST) results. Time-to-diagnosis was around four weeks. This optimised TB sequencing pipeline requires less time and expertise to run and analyse than Illumina, takes less time than phenotypic DSTs and the results are comparable with Illumina. The cost per sample is comparable with other methods. These features make it an important tool for incorporating into routine DR-TB diagnostic pipelines and larger scale drug resistance surveillance in all settings.